ROBOT TRAJECTORY PLANNING BASED ON 4-1-4 SPLINE INTERPOLATION WITH THE SAME INTERPOLATION TIME - XIONG RuiYang; JIA JianPin; HU RongHua; YUAN XinLiang; GUO FuMin (Jixie qiangdu)
A new type of upper extremity exoskeleton rehabilitation robot is designed,which have 5-degree of freedom.Firstly,the mechanical structure of the robot is analyzed. D-H coordinates of the robot are established based on D-H parameter method.According to its coordinates,its kinematics equation is obtained. In order to make the rehabilitation training in patients with comfort and stability,point out a linear interpolation function of quartic polynomial that based on the same time interpolation points,the purpose is to plan the trajectory of the upper limb exoskeleton rehabilitation robot. Finally,trajectory planning of multiple joints and drawing images are carried out.In ADAMS,the upper extremity exoskeleton rehabilitation robot based on 1: 1 model is simulated to verify the correctness of the function.By Analysing of trajectory planning parameters for single and multiple joints,then the results are compared with the simulation data in ADAMS to prove the feasibility and stability of this method,which can be used in the trajectory planning of rehabilitation robot.